Strategies for managing IS/IT personnel - Igbaria, Magid, 1958-; Shayo, Conrad; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
This title collects and presents key research articles focused on identifying, defining, and measuring accomplishment in knowledge management. A significant collection of the latest international findings within the field, this book provides a strong reference for students, researchers, and practitioners involved with organizational knowledge management.
13. Reluctance to report reality in troubled technology projects / Jo Ellen Moore, Lisa A. Burke -- 14. Important human factors for systems development success : a user focus / Tor Guimaraes, D. Sandy Staples, James D. McKeen.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 19, 2010).
Keywords: Electronic data processing personnel -- Recruiting; Electronic data processing personnel -- Training of; Electronic data processing departments -- Personnel management; High technology industries -- Employees -- Recruiting; High technology industries -- Personnel management; Employee retention; Personnel management; Electronic books